Institutional pressures and green supply chain integration intention: Evidence from Chinese manufacturing firms - Bochen Zhang; Shukuan Zhao; Dong Shao; Xueyuan Fan; Shuang Wang (PLoS ONE, 2025)
Green supply chain integration has become the key for manufacturing firms to cope with environmental challenges and gain sustainable competitiveness, but increasing the intention of firms to implement green supply chain integration is still a significant challenge. To respond to this issue, this study aims to theoretically discuss and empirically investigate the influence mechanism of institutional pressures on corporate green supply chain integration intention based on the theory of planned behavior. This study used a survey method to collect data from Chinese manufacturing firms, and the 292 finalized responses were analyzed using SPSS and AMOS. The findings indicate that institutional pressures, i.e., coercive and normative pressures, positively affect firms’ intention to implement green supply chain integration. The study also exposed the executives’ environmental awareness positively moderates the effect of coercive and normative pressures on green supply chain integration intention. Furthermore, executives’ self-efficacy positively moderates the effect of normative pressure on green supply chain integration intention. The findings of this study help deepen the understanding of the formation mechanism of green supply chain integration intention, which provides practical insights for effectively promoting green supply chain integration and realizing green transformation and high-quality development of manufacturing enterprises.